Data-mining the diaryl(thio)urea conformational landscape: Understanding the contrasting behavior of ureas and thioureas with quantum chemistry - Luchini, G; Ascough, D; Alegre-Requena, J; Gouverneur, V; Paton, R (Elsevier, 2018)
The conformations adopted by urea and thiourea functional groups influence catalysis and binding. We combine data-mining with quantum chemical calculations to understand the differences in conformational behavior for these two important structural motifs. We developed a Python tool to automate the compilation of X-ray structural information and perform conformational clustering and visualization, based on SMILES input. While diarylureas have an overwhelming preference for the anti,anti-conformer, diarylthioureas adopt a mixture of anti,anti- and anti,syn-conformers. Computations show the anti,anti-thiourea conformer is destabilized by out-of-plane rotations which avoid a steric clash with the sulfur atom. These conformational preferences were studied computationally under a variety of conditions, and apart from in the gas-phase, a preference for anti,anti-ureas was found. Consistent with experiments, this preference increases in more polar environments. Quantitative predicted ratios are sensitive to the computational treatment of solvation effects, with COSMO-RS giving more realistic amounts of the anti,anti-conformer in THF and DMSO.